SafAIRway: an airway training for pulmonologists performing a flexible bronchoscopy with nonanesthesiologist administered propofol sedation. Issue 23 (June 2016) - Schulze, Melanie; Grande, Bastian; Kolbe, Michaela; Kriech, Sarah; Nöthiger, Christoph B.; Kohler, Malcolm; Spahn, Donat R.; Franzen, Daniel
Abstract : Abstract: Nonanesthesiologist administered propofol (NAAP) sedation for flexible bronchoscopy is controversial, because there is no established airway management (AM) training for pulmonologists. The aim was to investigate the performance and acceptance of a proposed AM algorithm and training for pulmonologists performing NAAP sedation. The algorithm includes using 3 maneuvers including bag mask ventilation (BMV), laryngeal tube (LT), and needle cricothyrotomy (NCT). During training (consisting of 2 sessions with a break of 9 weeks in between), these maneuvers were demonstrated and exercised, followed by 4 consecutive attempts to succeed with each of these devices. The primary outcome was the improvement of completion time needed for a competent airway. Secondary outcomes were the trainees' overall reactions to the training and algorithm, and the perceptions of psychological safety (PS). The 23 staff members of the Department of Pulmonology performed a total of 552 attempts at AM procedures (4 attempts at each of the 3 maneuvers in 2 sessions), and returned a total of 42 questionnaires (4 questionnaires were not returned). Median completion times of LT and NCT improved significantly between Sessions 1 and 2 ( P = 0.005 and P = 0.04, respectively), whereas BMV was only marginally improved ( P = 0.05). Trainees perceived training to be useful and expressed satisfaction with this training and the algorithm. The perception of PS increased after training. An AM algorithm and training for pulmonologists leads to improved technical AM skills, and is considered useful by trainees and raised their perception of PS during training. It thus represents a promising program. Abstract : Supplemental Digital Content is available in the text